HISTORICAL CRITICAL ENVIRONMENTAL EDUCATION: A COLLECTIVE CONSTRUCTION - Agudo, Marcela de Moraes; Campos Tozoni-Reis, Marilia Freitas de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2020)
This theoretical study seeks to discuss the necessary collective construction that involves historical-critical environmental education. Environmental education based on Critical Historical Pedagogy has been constituted in the last years as a critical perspective radically supported by historical-dialectical materialism. The Grupo de Pesquisa em Educacao Ambiental - Environmental Education Research Group (GPEA), linked to the Postgraduate Program in Education for Science, Faculty of Science, Universidade Estadual Paulista (UNESP), Bauru Campus, in its production, individual and collective, has been dedicated to it deepening of critical historical environmental education. So, in this context, we will try to approach some points of environmental education from the Critical Historical Pedagogy, as a process of collective construction that comes in the last years of the most intense way, as the relationship between the critical historical pedagogy and curricular school contents; the relationship between society and environmental as an interdisciplinary object of environmental education; and initial reflections on the contents of critical historical environmental education. Thus, the relationship between society and the environment as an interdisciplinary object of investigation and the unity between contents and the form of environmental education are keys to the collective construction of critical environmental education, based on historical-dialectical materialism and historical-critical pedagogy. Therefore, we emphasize the need to continue the process of producing knowledge with the aim of deepening the relationship between content and form in the historical-critical pedagogical practice.
Keywords: Environmental education; Historical-critical pedagogy; Historical-dialectical materialism